2021
DOI: 10.1016/j.nmni.2021.100905
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in COVID-19

Abstract: The coronavirus disease (COVID-19) is a novel emerging infectious disease spreading worldwide. To further understand the disease, we compared its clinical characteristics, symptoms, and outcomes by gender. In an analysis of public surveillance data of Taiwan from January 21 to April 18, 2020, a total of 398 patients were diagnosed with COVID-19 by the detection of severe acute respiratory syndrome coronavirus 2 in pharynx swabs. We divided the patients into two groups: men and women. The associated data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
9
1
1
Order By: Relevance
“…Of note, we found in lungs, males display a higher differential expression of genes associated with activated neutrophils and alveolar macrophages and with the release of pro-inflammatory cytokines associated to ARDS, such as Il-6, Cxcl10 and Ifn □. This sex-based difference has been evidenced in human COVID-19 cases 6669 but it had not been previously reported for animal models, where the transcriptome of infected hamsters was mainly investigated using RT-qPCR rather than RNA-Seq analysis 53,70,71 . Another peculiarity of male hamsters standing out from our data is the differential expression of genes promoting angiogenesis (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Of note, we found in lungs, males display a higher differential expression of genes associated with activated neutrophils and alveolar macrophages and with the release of pro-inflammatory cytokines associated to ARDS, such as Il-6, Cxcl10 and Ifn □. This sex-based difference has been evidenced in human COVID-19 cases 6669 but it had not been previously reported for animal models, where the transcriptome of infected hamsters was mainly investigated using RT-qPCR rather than RNA-Seq analysis 53,70,71 . Another peculiarity of male hamsters standing out from our data is the differential expression of genes promoting angiogenesis (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…The incubation period did not differ significantly by gender, age group, and epidemic period which is in line with a previous study (8). However, another previous study demonstrated that the mean incubation period for male patients (8.0 days) was longer than that for female patients (4.8 days) (21). Regarding age, another study reported a significantly longer median incubation period for elderly patients over 60 years (7.7 days) than for young patients under 30 years (4.0 days) (22).…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with other studies, this finding shows that women have a higher perceived risk of infection compared to men [ 25 , 26 ]. This fact is contradictory to the gender consequences, which show a higher risk of severity [ 27 ] and mortality in men [ 28 ].…”
Section: Discussionmentioning
confidence: 97%